Restoring The Rights Of Child Victims Of Sexual Crimes In Indonesia Throughs Victim Impact Statement - Silitonga, Tumpal Paskalis (Law Research Review Quarterly, 2025)
The position of victims in the Indonesian Criminal Justice System currently seems to have been "discriminated against" by criminal law and the criminal justice system itself, this is due to the lack of regulations that pay attention to the rights and interests of victims, both in the form of protection and restoration of their rights, One of which is that victims are still unable to actively participate in defending their rights fairly because the role of victims is only as evidence in the form of victim witness statements in trials in their own cases. Likewise with children who are victims of sexual crimes in Indonesia who currently still need serious attention from the state, based on existing facts and data, it has been proven that the state is still unable to fulfill and restore the rights of child victims of sexual crimes fairly. So the researcher analyzes how the Victim Impact Statement can be the answer to the problems regarding victims today. This study applies a type of juridical-normative legal research with a qualitative approach. This study applies primary, secondary and tertiary legal materials as study materials. This study found that with the recommendation of the Victim Impact Statement which is based on the 'right to be heard', just as the accused can provide their perspective in providing justification or defense for themselves, the victim also has the right to convey an opinion or statement from the victim's perspective regarding the crime they experienced to be used as a consideration by the judge in making a fair and balanced decision, both for the victim and the accused.